Para-Diplomacy in the Protection of Indonesian Migrant Workers A Study on the Policy of East Java Province - Budi Raharjo; Arie Fitria; Vesela Radovic; Adibah Sayyidati; Himawan Estu Bagijo (Journal of Indonesian Legal Studies, 2026)
From 2019 to 2024, East Java remained Indonesia’s largest contributor of Indonesian Migrant Workers (PMI) and received the Indonesian Migrant Worker Award for six consecutive years. Despite this achievement, PMI continue to face human trafficking, violence, labor rights violations, and digital scam exploitation. These challenges are compounded by budget constraints and overlapping responsibilities between central and regional governments. This study examines the role of the East Java Provincial Government in PMI placement and protection through the perspectives of para-diplomacy and multi-level governance. Using a qualitative approach, data were collected through in-depth interviews and document analysis, emphasizing collaboration among government institutions, non-state actors, diaspora communities, and civil society. The findings show that effective migrant worker protection depends on multi-level and multi-actor collaboration. Triangulation involving political actors, government agencies, diaspora organizations, and NGOs reveals a persistent gap between formal regulations, including Law No. 18/2017 and Local Regulation No. 2/2022, and their implementation. Nevertheless, several good practices have emerged, such as integrated one-stop services, helpdesks, mobile information units, Village Migration Regulations, and Productive Migrant Villages. Community-based coordination has also strengthened legal advocacy, repatriation, and migration literacy. Based on these findings, the study proposes a Hybrid Community-Based Protection System that integrates state mechanisms with community and diaspora networks through a bottom-up approach. The research contributes to para-diplomacy and legal pluralism theories by highlighting non-state actors as key agents in migration literacy, legal protection, and socio-economic empowerment, while offering practical recommendations for regional policy innovation, cross-sector coordination, and digitalized migrant worker protection systems.